MENINGKATKAN SIKAP TANGGUNG JAWAB ANAK MELALUI METODE PROYEK DI TAMAN KANAK-KANAK TARBIYATULATHFAL UIN ANTASARI BANJARMASIN - Herlianti Herlianti; Samdani Samdani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Responsibility is the ability to set an attitude towards an act or task that is carried out or demands for the completion of a task, responsibility not only for oneself but also for others. This study aims to determine the activities of children in an effort to increase the attitude of children's responsibility through the project method for children aged 5-6 years in kindergarten. Tarbiyatul Athfal UIN Antasari Banjarmasin. This research is a type of classroom action research which is carried out for 2 cycles, each cycle consists of planning, implementing, observation, and reflection. The research subjects are children aged 5-6 years in kindergarten Tarbiyatul Athfal Banjarmasin, totaling 13 children. Data collection techniques through observation, documentation. Data analysis uses a combination of qualitative and quantitative approaches. The results showed that the results of the study on the development of children's responsible attitudes showed an increase in development, in the first cycle there were 7 children or about 53.8% who reached the category of developing according to expectations and developing very well. In the second cycle there were 11 children or about 84.62% who reached the category of developing according to expectations and developing very well. The results of achieving success indicators in cycle II have reached the expected completeness target, which is 80% of children in the complete category.